Intellectual Capital Performance : A Case Study of Public Sector Banks in India - Himanshu; Madhur (Indian Journal of Finance, 2020)
This paper aimed to study the intellectual capital performance of public sector banks of India for the time period from 1998 – 2017 using the VAIC model. The findings suggested that intellectual capital performance of public sector banks of India had a mixed trend during the period of study. However, on examining, it was observed that the PSBs were found to be poor performers. The government should take stern measures to improve intellectual capital performance in order to survive in an intellectual economy.